Evaluasi Tata Kelola Sistem Informasi Manajemen Sekolah dan Data Peserta Didik Berdasarkan Framework COBIT 2019 di SMAN 1 Medan - Oktaviana Bangun; Utari Adelia Citra; Chindy Olivia Melani; Putri Yolanda Purba; Ramadina Sofia Amadea (Universitas Mandiri Bina Prestasi, 2026)
The purpose of this study is to evaluate the School Management Information System and student data governance at Medan 1 Public High School (SMAN 1 Medan) using the COBIT 2019 framework. The evaluation was conducted across three key domains: grade and NISN (National Student Identity Number) data integrity (DSS06), e-learning availability (DSS05), and student data security. A quantitative approach was employed, with data collected through questionnaires, interviews, and direct observation of operational systems. The survey participants consisted of 45 individuals, including the principal, vice principal, teachers, IT staff, and system administrators. The analysis indicated that SMAN 1 Medan's IT governance maturity was at